Kajian Monitoring dan Evaluasi Pamsimas Kota Semarang - Indraya, Indraya; Santoso, Aprih (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
The PAMSIMAS program involves community participation, where the community receiving the program acts as the main actor and determinant in the entire process of preparation, planning, implementation and maintenance of the program. The aim of the study is to analyze monitoring and evaluation of pamsimaa in the city of Semarang. The analysis methods are quantitative and qualitative. The results of the research are that it is difficult for people to get clean water in the dry season because the dug wells owned by the residents are dry and murky. However, after receiving assistance from the PAMSIMAS program, the community felt that access to clean water facilities had increased. Another impact on the adequacy of clean water was that 75% of participants stated that after PAMSIMAS their clean water needs were met. During the rainy season, the community's wells are full, so most of the PAMSIMAS water is used by the community only for washing motorbikes, watering plants, or washing dishes. However, some people still use it for daily needs, even for drinking water as usual. Maintenance and management of facilities. The management body is a form of community participation in maintaining water availability after providing facilities. The community is asked to manage its own facilities, so a body consisting of community members is formed to maintain, monitor the development and repair of the facilities